A Note on the Discrete Spectrum of Gaussian Wells (I): The Ground State Energy in One Dimension. (29th February 2016) - Muchatibaya, G.; Fassari, S.; Rinaldi, F.; Mushanyu, J.
Abstract : The ground state energyE 0 ( λ ) ofH λ = - d 2 / d x 2 - λ e - x 2 is computed for small values ofλ by means of an approximation of an integral operator in momentum space. Such an approximation leads to a transcendental equation for whichϵ 0 ( λ ) = | E 0 ( λ ) | 1 / 2 is the root.